What did the public think of health services reform in Bangladesh? Three national community-based surveys 1999-2003 - Hossain Md Zakir; Milne Deborah; Andersson Neil; Cockcroft Anne; Karim Enamul (BMC, 2007)
Abstract Background Supported by development partners, the Government of Bangladesh carried out a comprehensive reform of health services in Bangladesh between 1998 and 2003, intended to make services more responsive to public needs: the Health and Population Sector Programme (HPSP). They commissioned a series of surveys of the public, as part of evaluation of the HPSP. This article uses the survey findings to examine the changes in public opinions, use and experience of health services in the period of the HPSP. Methods We carried out three household surveys (1999, 2000 and 2003) of a stratified random sample of 217 rural sites and 30 urban sites. Each site comprised 100-120 contiguous households. Each survey included interviews with 25,000 household respondents and managers of health facilities serving the sites, and gender-stratified focus groups in each site. We measured: household ratings of government health services; reported use of services in the preceding month; unmet need for health care; user reports of waiting times, payments, explanations of condition, availability of prescribed medicines, and satisfaction with service providers. Results Public rating of government health services as "good" fell from 37% to 10% and the proportion using government treatment services fell from 13% to 10%. Unmet need increased from 3% to 9% of households. The proportion of visits to government facilities fell from 17% to 13%, while the proportion to unqualified practitioners rose from 52% to 60%. Satisfaction with service providers' behaviour dropped from 66% to 56%. Users were more satisfied when waiting time was shorter, prescribed medicines were available, and they received explanations of their condition. Conclusion Services have retracted despite increased investment and the public now prefer unqualified practitioners over government services. Public opinion of government health services has deteriorated and the reforms have not specifically helped the poorest people. User satisfaction could be increased if government doctors improved their interaction with patients and if waiting times were reduced by better management of facilities.